Monitoring antimicrobial drug residues in an antibiotic-free poultry supply chain - Dalia Curci; Luigi Danesi; Giulia Rampazzo; Maria Nobile; Sergio Ghidini; Luca Chiesa; Francesco Arioli; Sara Panseri (Italian Journal of Food Safety)
With poultry consumption projected to rise significantly, understanding the presence and control of antimicrobial residues in poultry products becomes increasingly important for ensuring food safety and public health. Consequently, in the present study, the incidence and concentration of antimicrobial drugs in 919 samples, all from an antibiotic-free poultry supply chain, were investigated using a high-pressure liquid chromatography high-resolution mass spectrometry multiclass antimicrobic residue method, involving a wide range of matrices (water, feed, feathers, livers, muscles, eggs, and retail products, such as chicken nuggets, chicken drumsticks, chicken breast, and chicken thighs) to verify not only the compliance with Regulation 37/2010, but also to investigate the possible administration of antimicrobial drugs or potential bad farm management in the antibiotic-free supply chain. Antimicrobial drug residues were detected in 4% of all the analyzed samples, with concentrations ranging from < detection capability to 57.87 ng g-1, but no residues were detected in muscles, livers, eggs, and retail products (chicken nuggets, chicken drumsticks, chicken breast, and chicken thighs). While the absence of antimicrobic residues in these matrices suggests compliance with maximum residue limits set by Regulation 37/2010 and a framework of substantial safety towards consumers, the presence of antimicrobic residues in drinking water, feathers, and feed, considering the provenience from an antibiotic-free supply chain, highlights the importance of the ongoing monitoring activities to ensure that the results align with antibiotic-free product certification standards.